2021
DOI: 10.1002/anie.202110028
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Function‐Oriented Core–Shell Nanostructures in Hydrogen‐Bonded Organic Frameworks for Near‐Infrared‐Responsive Bacterial Inhibition

Abstract: Exploration of effective ways to integrate various functional species into hydrogen‐bonded organic frameworks (HOFs) is critically important for their applications but highly challenging. In this study, according to the “bottle‐around‐ship” strategy, core–shell heterostructure of upconversion nanoparticles (UCNPs) and HOFs was fabricated for the first time via a ligand‐grafting stepwise method. The UCNPs “core” can effectively upconvert near‐infrared (NIR) irradiation (980 nm) into visible light (540 nm and 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 71 publications
0
45
0
Order By: Relevance
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Beyond that, being metal free, HOFs have lower toxicity and better biocompatibility than the MOF counterparts. In view of the above-mentioned merits, HOFs have been widely exploited as multifunctional materials for gas storage and separation, sensing, heterogeneous catalysis, proton conduction, , biological applications, etc. The development of HOFs, however, still far lags behind their MOF and COF counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…As the promising antibacterial methods, phototherapeutic strategies including photodynamic therapy (PDT) and photothermal therapy (PTT) have captured our eyes, which employ photosensitizers (PSs) to absorb light, and then produce reactive oxygen species (ROS) or thermal energy to kill microbial pathogens with the advantage of noninvasiveness, few adverse effects, and high efficiency. On the other hand, nanozymes, nanomaterials to convert enzyme substrates to enzyme products, have also drawn increasing attention due to their efficient ROS generation and broad-spectrum bactericidal activity. For example, some nanomaterials can convert endogenous hydrogen peroxide to a toxic hydroxyl radical ( • OH) in organisms to inhibit bacterial viability (called peroxidase-like, POD). , Although synergistic actions of the above phototherapy methods for antibacterial properties have been explored, , most of the previous antibacterial agents need to be postmodified or orderly assembled by multimaterials with different phototherapy effects, which often requires complex procedures and also brings challenges to the overall stability of the final assembled products. , Moreover, previous composites employed for antibacterial infection usually needed irradiation with different excitation lights . The preparation of a material alone with multiple phototherapeutic properties under single NIR irradiation is of great significance to solve this problem.…”
Section: Introductionmentioning
confidence: 99%